Gazociąg północny – inwestycja ekonomiczna czy polityczna? Komentarze w prasie polskiej i niemieckiej - Jarosz, Adam (Historia i Polityka, 2010)
North Stream - economical or political investment? Comments in Polish and German press The article shows the press debate in Germany and Poland about political and economical aspects of the Baltic pipeline. On the example of about sixty articles from four German and four polish newspapers and magazines the question was answered, if this investment was an economical or pure political project. The commentators in both countries were widely describing and commenting this issue, and were clearly suggesting that the North European Gas Pipeline was a political project or even a part of a Kremlin strategy of rebuilding their lost empire. The climax of the debate occurred to be the turn of the years 2005 and 2006, when Russia "turned off the gas valve” to the Ukrainę. The event reasoned a panie among the publicists of both Polish and German media. There were many suggestions and itwas spoken about a elear blackmail from the Kremlin side. Ithas to be mentioned that all the press sources were in accordance to each other, no matter what their political sympathies were. Polish publicists tried to show that the pipę was pointless from the economical point of view, presenting huge costs and big technical problems of building beneath the sea. Despite that, also the supporters of the investment had chance to presenttheir opinions in the polish media. German journalists pointed outthe advantages of the investment, which were the alternative way of supplying gas with omitting the "unreliable” countries like the Ukrainę or Belarus, competition for resources with China and India or the plans of creating a central distribution point of Russian gas for the all Europę in Germany. The debate showed as well big controversies and concerns which the Baltic pipeline aroused. Even though the supporters and builders ofthis project tried to persuade the public opinion that the pipeline is an economical project, hardly anybody believed that and some newspapers responded to it with polemics or even ironies.